Exploration of YouTube Marketing Communication: Brand Awareness, Brand Image, Brand Trust, and Purchase Intention in the Millennial Generation - Pratama, Iyus; Astuti, Puji (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
In the current era of modernization, advertising is very important for a marketing process. Various types of media can be used to advertise, one of which is on the YouTube platform, which incidentally is the largest digital media today. Advertisements on YouTube (youtube ads) will grow purchase intentions reinforced by brand awareness, brand image and brand trust. The purpose of this research is to explore YouTube marketing communication: brand awareness, brand image, brand trust and purchase intention among the millennial generation in Jabodetabek (Jakarta, Bogor, Depok, Tangerang dan Bekasi). This research was conducted on 309 YouTube user respondents who had seen YouTube advertisements with smartphone brand content (Samsung, Vivo and Oppo). Data collection was obtained through questionnaires that were distributed online using the Google Form media. I use the Lisrel Structural Equation Model (SEM) to test this research model. The results of this study indicate that YouTube ads have a positive effect on brand awareness, brand awareness has a positive effect on purchase intentions, YouTube ads have a positive effect on brand image, brand image has a positive effect on purchase intentions, YouTube ads have a positive effect on purchase intentions. Brand awareness has a positive effect on brand trust and trust has a positive effect on purchase intention.